Автоматичне настроювання позиційної системи управління робототехнічним пристроєм із замкненою кінематикою - Старостін, Сергій Станіславович; Сергієнко, Ганна Сергіївна (НТУ "ХПІ", 2010)
The paper deals with the questions of a self-tuning of position control systems with linear motors. The self-tuning is performed on the basis of object parameter identification. For the parameter identification the motor driving force is created as a function of motion direction and friction force. The laboratory experiments have shown the achievements of desirable performances.
Self-tuning of a position control system for a robotic object with closed kinematics chain
Keywords: схема кінематична; регулювання; ідентифікація